Targeting Apoptosis Pathways in Cancer with Alantolactone and Isoalantolactone - Azhar Rasul; Muhammad Khan; Muhammad Ali; Jiang Li; Xiaomeng Li (The Scientific World Journal)
Alantolactone and isoalantolactone, main bioactive compounds that are present in many medicinal plants such as Inula helenium, L. Inula japonica, Aucklandia lappa, Inula racemosa, and Radix inulae, have been found to have various pharmacological actions including anti-inflammatory, antimicrobial, and anticancer properties, with no significant toxicity. Recently, the anticancer activity of alantolactone and isoalantolactone has been extensively investigated. Here, our aim is to review their natural sources and their anticancer activity with specific emphasis on mechanism of actions, by which these compounds act on apoptosis pathways. Based on the literature and also on our previous results, alantolactone and isoalantolactone induce apoptosis by targeting multiple cellular signaling pathways that are frequently deregulated in cancers and suggest that their simultaneous targeting by these compounds could result in efficacious and selective killing of cancer cells. This review suggests that alantolactone and isoalantolactone are potential promising anticancer candidates, but additional studies and clinical trials are required to determine their specific intracellular sites of actions and derivative targets in order to fully understand the mechanisms of therapeutic effects to further validate in cancer chemotherapy.